Status of Kiswahili Remedial Teaching Exercise in Public Secondary Schools in Temeke Municipality, Tanzania - Shukuru Lukas; Prospery M. Mwila (PT. Pusmedia Group Indonesia, 2025)
Remedial teaching strengthens students' basic academic skills, such as the ability to read, write, analyse, and interpret. It also assists students who struggle in certain subjects to catch up and master areas not mastered before, empowers students who lag, develops interpretation skills, and helps students with critical thinking skills. This study was guided by a mixed approach and a cross-sectional survey design to analyse the status of Kiswahili remedial teaching in Temeke Municipality public secondary schools. The sample size of this study was 131 participants selected from ten secondary schools, including 10 heads of schools, 20 Kiswahili teachers, 100 students, and 1 municipal education officer selected from the population through simple random and purposive sampling. Questionnaires and interviews were used to collect data from the participants. The results reveal that the Kiswahili remedial teaching intervention enables facilitators and students to correct learning problems, enhance coverage of the subject matters that were unable to be completed in the classroom teaching and learning process, prepare learners for their final examinations, and help slow-learning students and those falling behind in their learning at school and those at risk of dropping out of studies. Moreover, the study finds that teaching material, lack of motivation, and overcrowded classes hinder much progress in students’ performance. apart from ensuring the availability of learning resources, remedial teachers should fulfil the requirement of getting to know each of their students personally to delve into the depths of their souls and consider the external details of their life.